Synthesis and anticancer activity of new heterocyclic derived from diaryl β-lactam supported by molecular docking and toxicity LD50 - Mohammed Fadhil Hassan; Duaa Qassim kamil; Thaer khazaal makki; Muqdad Irhaeem Kadhim; Hussein Ali Kadhim Kyhoiesh (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
A novel compound called 3-chloro-4-(4-(dimethylamino)phenyl)-1-(6-methoxybenzo[d]thiazol-2-yl)azetidin-2-one (3-CDBA), derived from beta-lactams, was investigated for its effects on human leukemia (HL-60) cells, pancreatic cancer (TCP-1026) cells, and healthy cells (WRL68) for comparison. The compound showed an inhibitory concentration (IC50) of 91.55 µg/ml on the leukemia cells, 141.3 µg/ml on the pancreatic cancer cells, and 353.8 µg/ml on the healthy cells. This indicates that the compound selectively kills cancer cells while having minimal effect on healthy cells, as higher concentrations are required to kill half of the healthy cells. These findings suggest that the compound has the potential to inhibit the growth of cancer cells. In comparison to conventional antioxidants like ascorbic acid (vitamin C), the beta-lactam derivative (3-CDBA) exhibited a higher percentage of inhibition at the highest concentration, with a value of 72.95% and an IC50 of 42.67 µg/ml. Furthermore, the compound's effects were studied on two types of pathogenic bacteria, specifically Staphylococcus aureus (positive) and Escherichia coli (negative), as well as various Penicillium species. The compound showed the greatest inhibitory effect at a concentration of 1000 µg/ml. In a theoretical examination, molecular docking was employed to design and synthesize a drug using the beta-lactam derivative and a target associated with cancer cells from a protein database. The compound demonstrated a strong and close interaction with amino acids and different sites within the active pocket, resulting in a higher binding energy. This indicates that the compound has the potential to inhibit the growth of cancer cells by disrupting their metabolic processes. To determine the lethal dose (LD50), the beta-lactam derivative (3-CDBA) was administered to half of the animals in the study.